PENGARUH INDEPENDENSI, PROFESIONALISME DAN PENGALAMAN KERJA DALAM KINERJA AUDITOR - Christina Sososutiksno (JURNAL LENTERA AKUNTANSI, 2022)
The purpose of this study was to determine the Effect of Independence, professionalism, and Work Experience on Auditor Performance in the Inspectorate of Maluku and Ambon City. This research method is quantitative research. The sample used is functional auditors work in the inspectorate of Maluku and Ambon City as 40 respondent. Data analysis method is SPSS version 22. The result of this study indicate independence and professionalism have effect on auditor performance, but work experience have not effect on auditor performance.Key words: Independence, Proffesionalism, Work Experience, Auditor Performance